CALIFORNIA PROP 65 UPDATE - DICKSON RB # PAUL HASTINGS JANOFSKY WALKER; SCHMIDTPRAUL LJ (Tufts Archival Research Center, 2007)
Update on California proposition 65 which prohibits the discharge of toxins into the water as well as prohibiting companies knowingly exposing people to carcinogenic toxins without a proper warning. Discusses the process for adding a chemical onto the list of toxins. Explains at length all of the components of the bill including warning procedures and the definition of a toxin.